2017
DOI: 10.1097/ico.0000000000001301
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Endothelial Cell Loss in Preloaded Descemet Membrane Endothelial Keratoplasty Grafts

Abstract: Purpose Availability of preloaded DMEK (pDMEK) tissue may increase acceptance of DMEK in surgical management of endothelial disease. The goal of this study is to determine the safety of pDMEK grafts for 24 hours prior to surgery by analyzing endothelial cell loss (ECL) using two image analysis software programs. Methods Eighteen cadaveric corneas were prepared for DMEK using a standardized technique and loaded in a modified jones tube injector. Nine of the corneas were injected into Calcein AM vital dye afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The mean corneal endothelial cell damage rate was 16.8 ± 5.9% in the donor corneas previously loaded into a Jones tube and 9.3 ± 5.9% in non-preloaded corneas. Wholle et al [10] evaluated the endothelial cell damage of preloaded DMEK grafts to determine the safety of preloaded DMEK grafts for 24 hours before surgery by analyzing endothelial cell loss. They loaded 18 corneas into a modified Jones’ tube that had been filled with Optisol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean corneal endothelial cell damage rate was 16.8 ± 5.9% in the donor corneas previously loaded into a Jones tube and 9.3 ± 5.9% in non-preloaded corneas. Wholle et al [10] evaluated the endothelial cell damage of preloaded DMEK grafts to determine the safety of preloaded DMEK grafts for 24 hours before surgery by analyzing endothelial cell loss. They loaded 18 corneas into a modified Jones’ tube that had been filled with Optisol.…”
Section: Discussionmentioning
confidence: 99%
“…Since their report, many researchers have reported the degree of corneal endothelial cell damage from experimental donor punches, donor preparations, and lamellar keratoplasty procedures using various corneal staining solutions for donor corneas not suitable for keratoplasty in patients. [5–10]…”
Section: Introductionmentioning
confidence: 99%
“…In their study involving 31 DMEK grafts, Tran et al reported that tissue preloading incurred more endothelial cell loss than simply prestripping tissue 13. Studies have also found greater cell loss in the S-stamp area in preloaded DMEK grafts, often with complete loss of all cells in the stamped area 14. DMEK presents a steep learning curve and surgical skills that are entirely different from DSEK 8.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of cell loss in the samples peeled and removed as a scroll are consistent with the 22.0% and 19.2% rates of cell loss in groups measured by Wolle and colleagues using a comparable methodology of assessment. 4 It is notable that tri-folding resulted in significantly less cell loss in this study, which we believe may be due to the protection of an endothelium-in morphology during manipulation and staining. The data suggest that at the minimum, the additional manipulation of the periphery of the graft required for tri-folding does not appear to contribute to increased cell loss in the tri-folding group.…”
Section: Discussionmentioning
confidence: 55%